2019
DOI: 10.1088/1361-6633/ab2429
|View full text |Cite
|
Sign up to set email alerts
|

Horndeski theory and beyond: a review

Abstract: This article is intended to review the recent developments in the Horndeski theory and its generalization, which provide us with a systematic understanding of scalar-tensor theories of gravity as well as a powerful tool to explore astrophysics and cosmology beyond general relativity. This review covers the generalized Galileons, (the rediscovery of) the Horndeski theory, cosmological perturbations in the Horndeski theory, cosmology with a violation of the null energy condition, degenerate higher-order scalar-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
397
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(424 citation statements)
references
References 316 publications
9
397
0
Order By: Relevance
“…In the context of analytical mechanics, a simple example of degenerate higher-derivative system is given by [4,10,11]…”
Section: The Dhost Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of analytical mechanics, a simple example of degenerate higher-derivative system is given by [4,10,11]…”
Section: The Dhost Theoriesmentioning
confidence: 99%
“…Although generically the EL equations in such theories contain higher derivative terms, the appearance of Ostrogradsky ghosts [2] can be avoided using certain degeneracy conditions [3]. Degenerate higher-order scalar-tensor (DHOST) theories [4-9] (see also [10,11]) provide the most general framework of scalar-tensor theories which are free from Ostrogradsky instabilities [2], and hence the system contains only three degrees of freedom (DOFs), namely, two tensorial and one scalar polarizations (See § II for details). Applications of DHOST theories to cosmological and astrophysical problems have been investigated in Refs.…”
mentioning
confidence: 99%
“…The second reason is that nonlinear modifications of gravity have been introduced in attempts to address the discovery of dark matter, dark energy, solve the flatness and horizon problems of early universe cosmology, and resolve the issues of the initial cosmological singularity and singularities formed during gravitational collapse. EdGB is an important and representative member of a class of modified gravity theories, Horndeski theories, that have been invoked to solve these various issues within classical GR (for a recent review on Horndeski theories see [26]), and it thus is interesting to see if the theory is mathematically sensible as a classical field theory.…”
Section: Introductionmentioning
confidence: 99%
“…In [19], it is shown that (7) has a wide range of cosmological solutions, that may be relevant for the primordial universe, because it may be responsible, for instance, for a cosmological bounce. There is a debate concerning the relation between G 5 theories and gravitational waves, but it was already explored in several papers (see [8] and [20], for instance) and, for (7) in particular, it was addressed in detail in [19]. Taking into account that debate, one has to consider (7) as a contribution to the canonical Lagrangian for the minimal coupling in order to study stages of the evolution of the universe after inflation [19].…”
Section: Introductionmentioning
confidence: 99%